Drugs to prevent sudden cardiac death. (15th June 2017) - Erath, Julia W.; Hohnloser, Stefan H.
Abstract: Sudden cardiac death (SCD) remains a major public health burden despite enormous advances in post-resuscitation care, management of structural heart diseases, and antiarrhythmic treatment modalities. Primary and secondary prevention of sudden cardiac death require understanding of the underlying substrate causing ventricular arrhythmias and its modification by pharmacological (i.e. heart failure therapy) or interventional (catheter ablation) methods. Antiarrhythmic drug therapy has experienced ups and downs during the last 30 years balancing high antiarrhythmic potential, toxic side effects and pro-arrhythmic potency. Therefore, the implantable cardioverter-defibrillator (ICD) remains irreplaceable in primary and secondary prevention of SCD. Hybrid therapy combing antiarrhythmic drugs (predominantly amiodarone) with ICD therapy represents an often-used treatment option. This short review provides an overview of current pharmacological therapy aiming to prevent SCD.